Child care before 6 months of age: A qualitative study of mothers' decisions and feelings about employment and non-maternal care - Leach, P; Barnes, J; Nichols, M; Goldin, J; Stein, A; Sylva, K; Malmberg, L; Team, FCCC (2006)
Employment of women while their children are infants has increased in the UK in the last decade. This study of 57 employed mothers of infants less than seven months old examined their retrospective reports of planning child care and their contemporaneous feelings about the child care they were using, based on qualitative interviews. Issues addressed included mothers' reasons for returning to employment at that time, their theoretical preferences among a range of child care types and providers and the process of making actual choices, including the range and types of advice received and the involvement of fathers. Mothers were also encouraged to discuss their feelings about how child care was working out once the infant was settled. Continuing concerns expressed by mothers included the importance of open communication with caregivers, their desire to keep control over infants' daily lives and upbringing, worries about infants' safety and concerns about the levels of cognitive stimulation they received. Copyright © 2006 John Wiley and Sons, Ltd.